Proporsi Gluten Dan Tepung Kacang Hijau (Vigna Radiata L) Pada Pembuatan Daging Tiruan (Meat Analog) Ditinjau Dari Sifat Organoletptik - Tri Wahyu Ramadhan; Lilis Sulandari; Nugrahani Astuti; Ila Huda (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Artificial meat is a diversified food product made from vegetable protein. The vegetable protein used comes from gluten and mung bean flour. The purpose of this study was to determine: 1) determine the best proportion of gluten and mung bean flour in making artificial meat in terms of the organoleptic properties of artificial meat; 2) the nutritional content of artificial meat from the best proportion of gluten and mung bean flour. This type of research is an experiment with three different treatments (70%: 30%, 80%: 20%, 90%: 10%) which were tested on 30 panelists. The results of organoleptic properties were analyzed using a single ANOVA SPSS program and nutritional content was analyzed in the laboratory. The results of data analysis show: 1) The best proportion of the results of the organoleptic test is the proportion of 80%: 20% gluten and green bean flour with an average result of imitation meat shape 3.47 quite fibrous meat, color 3.53 brownish white, texture 4.3 quite chewy, aroma 3.37 slightly spicy aroma langu, taste 4.13 quite savory, and preference 3.5 like; 2) the results of laboratory tests of imitation meat with the proportion of gluten and green bean flour are ash content 1.24%, water content 11.82%, protein content 12.18%, fat content 2.31% / 100g.